Duration-dependent effects of social isolation on reintegration behavior in the swarming soldier crab, Mictyris guinotae - Ruijia Yang; Kentaro Eto; Takumi Nakano; Yukio Pegio Gunji (PLoS ONE, 2026)
Social contact is fundamental to the behavioral and physiological homeostasis of group-living animals. When such contact is disrupted, even briefly, individuals may undergo behavioral shifts that persist beyond the isolation period and alter their interactions upon reintegration into the group. The soldier crab Mictyris guinotae , which forms large, dense swarms on intertidal flats, provides a tractable natural system for studying how transient isolation affects subsequent reintegration into collective behavior. Unlike eusocial insects with stable social roles, M. guinotae exhibits flexible, non-hierarchical interactions, allowing individual perturbations to be examined without confounding effects of dominance or task specialization. We conducted two experiments to examine how different durations of enforced isolation influence subsequent reintegration into collective movement. Isolation periods ranged from 5 to 180 minutes, and behavioral parameters such as local polarity, movement distance, and nearest-neighbor proximity were compared with controls. Individuals isolated for 5–30 minutes exhibited increased locomotor activity and reduced nearest-neighbor distance relative to controls, whereas 3-hour isolation induced a biphasic pattern characterized by an initial reduction in movement followed by elevated activity that remained weakly coordinated with the swarm. These results reveal a non-linear, threshold-dependent effect of isolation in a non-eusocial, anonymous collective. The study establishes Mictyris guinotae as a tractable invertebrate system for examining how transient social disruption alters measurable individual-level behavior and propagates through local interactions to shape emergent group-level dynamics.